Enhancing soil liquefaction resistance and small-strain dynamic properties using cation-crosslinked biopolymer hydrogel - Park, Dong Yeup; Chang, Ilhan; Lee, Minhyeong; Cho, Gye Chun (Soil Dynamics and Earthquake Engineering, 2025)
In biopolymer-soil stabilization, biopolymers function in the soil either as viscous fluids or rigid gels. However, the influence of these hydrogel states on soil liquefaction resistance and their underlying mechanisms remain insufficiently understood. This study examines the seismic response of sand treated with biopolymers under small-to-medium strain cyclic loading, with a focus on the efficacy of Cr3+-crosslinked xanthan gum (CrXG) in mitigating liquefaction. Liquefaction resistance and dynamic properties of CrXG-treated soil were compared against thermogelation and non-gelling viscous biopolymer treatments using cyclic direct simple shear and resonant column tests. CrXG treatment at 1 % content improved liquefaction resistance (CRR10) from 0.088 to 0.687 by preventing shear strain accumulation and pore pressure buildup, with enhancing dynamic shear stiffness and delaying stiffness degradation and damping ratio changes to higher strain levels. In contrast, soils treated with non-gelling viscous XG exhibited limited reinforcement under large strain cyclic loading, showing earlier liquefaction and lower CRR10 compared than untreated sand, alongside reduced dynamic shear modulus and rapid stiffness degradation. Comparisons across varying earthquake moment magnitudes revealed that CrXG-treated soil achieved liquefaction resistance comparable to other soil stabilization methods and demonstrated greater improvement efficiency than thermogelation biopolymers requiring thermal treatment. These findings highlight the potential of CrXG as a sustainable and practical solution for improving liquefiable soil stability under seismic loading.
Keywords: Biopolymer-soil stabilization; Cation-crosslinked xanthan gum; Crosslinked; Cyclic simple shear; Damping ratio; Dynamic shear modulus; Dynamics properties; Liquefaction resistance; Soil stabilization; Treated soils; Biopolymer-soil stabilization; Cation-crosslinked xanthan gum; Cyclic simple shear; Damping ratio; Dynamic shear modulus; Liquefaction resistance